Mitochondria as a Therapeutic Target in Metabolic Disorders - Cai, Youde; Gan, Fang; Chen, Yunzhi; He, Qiansong; Chen, Wei; Peng, Zhongyong; Gong, Ling (Mini Reviews in Medicinal Chemistry, 2025)
Mitochondria, commonly termed the 'cellular powerhouse', produce the majority of cellular adenosine triphosphate (ATP) through oxidative phosphorylation (OXPHOS). In addition to their role in energy synthesis, mitochondria are crucial for maintaining calcium homeostasis, mediating cellular signaling, regulating cell proliferation and apoptosis, and supporting various other physiological processes. In recent years, mitochondria have gained prominence as a critical target for the treatment of metabolic disorders. Research has demonstrated a strong association between mitochondrial dysfunction and the pathogenesis of metabolic diseases, such as insulin resistance, diabetes, metabolic syndrome, cardiovascular diseases, and endocrine tumors. Consequently, understanding the mechanisms of mitochondrial homeostatic imbalance and developing mitochondria-targeted therapeutics hold promise for innovative treatments of metabolic disorder-related diseases. This article seeks to elucidate recent advancements in the understanding of mitochondrial dysfunction's role in metabolic diseases and offers a comprehensive overview of current therapeutic strategies and approaches for addressing this dysfunction.
Keywords: therapeutic target